Effects of Edentulism on Mandibular Morphology: Evaluation of Panoramic Radiographs - Rıdvan Okşayan; Bayram Asarkaya; Nizamettin Palta; İrfan Şimşek; Oral Sökücü; Eren İşman (The Scientific World Journal)
Purpose. The objective of this study was to evaluate morphological changes of the mandible in edentulous and dentate subjects using panoramic radiographs. Materials and Methods. Panoramic radiographs were divided into the following three groups: Group I (completely edentulous group), Group II (old dentate group) and Group III (young dentate group). The research parameters of gonial angle, condylar height, ramus height, ramus notch depth, and antegonial notch depth were measured on panoramic radiographs. The Kruskal-Wallis statistical test was used to determine significant differences in mandibular morphological parameters among the three groups. The Mann-Whitney U test was used to compare the subgroups. Results. Significant differences were found only in ramus height between three groups. According to the Mann-Whitney U test, a significant difference was exhibited among Groups I and II in the ramus height parameter. No significant differences were found in the gonial angle, condylar height, ramus notch depth, or antegonial notch depth when comparing the young dentate, old dentate, and completely edentulous subjects. Conclusions. Significant differences were found only in ramus height between the groups. Ramus height may be an indicator that changed by years and tooth loss. It must be considered that ramus height can be decreased in edentulism.